Persepsi Masyarakat Pesisir dalam Pengelolaan Ekosistem Hutan Mangrove di Muara Gembong Bekasi Jawa Barat - Yurizky Permata Sari; Messalina L. Salampessy; Ina Lidiawati (PERENNIAL, 2018)
Increasing population growth in coastal areas, resulting in increasing demand for land for settlements, plantations, aquaculture, and other uses. This causes a lot of mangrove land being damaged. This research aims to know the people's perceptions of the function and role of mangrove forests and the management of sustainable mangrove forest ecosystems. The location of sample data collection is in Pantai Bahagia Village, Muara Gembong District, West Java. The sampling technique used to assess community perceptions is a selected technique (purposive sampling) with 30 respondents. Community perception of the function and role of mangrove forests in Muara Gembong is in the high category. The community has experienced the negative impacts of mangrove forest degradation, such as tidal floods, fishpond damage, and sea water intrusion, so that the community is aware of the importance of the function and role of mangrove forests for the survival of the community in the future. Community perception of mangrove forest ecosystem management in Muara Gembong is in the high category. All losses experienced by the community, whether in the form of fishpond damage, road access, to residential houses, foster public awareness of the importance of sustainable management of mangrove forest ecosystems.Key words: Perception; Forest Management; Mangrove; Muara Gembon